Reconciling free trade, fair trade, and interdependence : the rhetoric of presidential economic leadership - Conti, Delia B. (Westport, CT : Praeger, 1998)
In this book, the author examines the rhetoric of trade policy and the implications for the rhetoric of intermestic issues.
Includes bibliographical references: p. 165-166 and index.
ne 24/01/2019
Loans
Keywords: Free trade; Presidents; Communication in politics; United States